Architecture of the Essential [comunicação oral] - Fonseca, Alexandra (2021)
"(...) I hope for a new awareness of the tactile dimensions of material and detail, light and space understood from the point of view of individual human experience - a phenomenology of architecture." Steven Holl (1991) From the contributions of three Alvar Aalto international symposiums, which took place in the nineties, one can perceive that the search for a more human architecture, that calls for a sensorial and tactile dimension, related above all to the individual human experience, is still being posed, and is still more relevant today than ever. Thus, this study intends, from a selected Alvar Aalto encounters, to underline the importance of the sensorial and phenomenological dimension in Architecture. The purpose of deepening these notions, is to select from a participant in this congress, Peter Zumthor, a specific case study where the theme under study is relevant. We intend to show how this issue of sensibility, an idea of Architecture conceived through spatial narratives - atmospheres - is essential for the better understanding of Contemporary Architectural discourses. Therefore, an interpretative reading is proposed around the Museum of the Archdiocese of Cologne, a work anchored in a particular place, context and author, whose main themes design options shape the building through architectural narratives, atmospheres, set on the condition of place and the meaning of programme. The proposed reading opens space for a more personal interpretation, covering in effect, a more sensorial perspective that is closely related to the themes summoned in the Alvar Aalto encounters. This study is part of a master thesis on MasterŽs Degree in Architecture, at FAUP, 2019/2020, under the supervision of Helder Casal Ribeiro.